2011
DOI: 10.5194/amtd-4-3891-2011-supplement
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supplementary material to "Inversion of tropospheric profiles of aerosol extinction and HCHO and NO<sub>2</sub> mixing ratios from MAX-DOAS observations in Milano during the summer of 2003 and comparison with independent data sets"

Abstract: SupplementThe first part of the supplement presents a modified version of Fig. 4. In contrast to the original figure, in Fig. S1 the error bars are shown for the retrievals assuming a box-profile (shape parameter = 1).The second part of the supplement (Figs. S2 -S11) presents the individual graphs of the correlation analyses between the MAX-DOAS results versus independent measurements as well as between MAX-DOAS results of the different telescopes.In the third part of the supplement, the results of the normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Understanding of current emissions (Martin et al, 2006), the performance of chemical transport models (Zyrichidou et al, 2009;Huijnen et al, 2010, and references therein) and changes in anthropogenic emissions (Stavrakou et al, 2008;Wang et al, 2012) have been studied using satellite retrieved NO 2 columns. Observations of NO 2 (Johansson et al, 2009;Wagner et al, 2010;Constantin et al, 2013) using the Differential Optical Absorption Spectroscopy (DOAS) technique (Noxon, 1975;Solomon et al, 1987) have been reported at various locations around the world and in several cases have been used for retrieving vertical profiles of atmospheric NO 2 and also for validating satellite observations (Hönninger et al, 2004;Frieß et al, 2006;Wagner et al, 2011;Hendrick et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of current emissions (Martin et al, 2006), the performance of chemical transport models (Zyrichidou et al, 2009;Huijnen et al, 2010, and references therein) and changes in anthropogenic emissions (Stavrakou et al, 2008;Wang et al, 2012) have been studied using satellite retrieved NO 2 columns. Observations of NO 2 (Johansson et al, 2009;Wagner et al, 2010;Constantin et al, 2013) using the Differential Optical Absorption Spectroscopy (DOAS) technique (Noxon, 1975;Solomon et al, 1987) have been reported at various locations around the world and in several cases have been used for retrieving vertical profiles of atmospheric NO 2 and also for validating satellite observations (Hönninger et al, 2004;Frieß et al, 2006;Wagner et al, 2011;Hendrick et al, 2014).…”
Section: Introductionmentioning
confidence: 99%